Peripartum Hysterectomy: Is There Any Difference Between Emergency and Planned Surgeries? - Tufan Oge; Vehbi Yavuz Tokgoz; Yusuf Cakmak; Melih Velipasaoglu (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective To compare the outcomes of emergency and planned peripartum hysterectomies. Methods The present retrospective cross-sectional study was conducted in two hospitals. Maternal and neonatal outcomes were compared according to emergency and planned peripartum hysterectomies. Results A total of 34,020 deliveries were evaluated retrospectively, and 66 cases of peripartum hysterectomy were analyzed. Of these, 31 were cases of planned surgery, and 35 were cases of emergency surgery. The patients who underwent planned peripartum hysterectomy had a lower rate of blood transfusion (83.9% versus 100%; p=0.014), and higher postoperative hemoglobin levels (9.9±1.3 versus 8.3±1.3; p<0.001) compared with the emergency hysterectomy group. The birth weight was lower, although the appearance, pulse, grimace, activity, and respiration (Apgar) scores were higher in the planned surgery group compared with the emergency cases. Conclusion Planned peripartum hysterectomy with an experienced team results in less need for transfusion and improved neonatal outcomes compared with emergency peripartum hysterectomy.